THEORY OF VIBRATORY MOBILIZATION ON NONWETTING FLUIDS ENTRAPPED IN PORE CONSTRICTIONS - Beresnev I.A. (My University, 2006)
Quantitative dynamics of a nonwetting ganglion of residual oil entrapped in a pore constriction and subjected to vibrations of the pore wall can be approximated by the equation of motion of an oscillator moving under the effect of the external pressure gradient, inertial oscillatory force, and restoring capillary force. The solution of the equation provides the conditions under which the droplet experiences forced oscillations without being mobilized or is liberated from its entrapped configuration if the acceleration of the wall exceeds an unplugging value. This solution provides a quantitative tool for estimating the parameters of vibratory fields needed to liberate entrapped, nonwetting fluids. For typical pore sizes encountered in reservoir rock, wall accelerations must exceed at least several m/s2 and even much higher levels to mobilize the droplets of oil; however, in the populations of ganglia entrapped in natural porous environments, many may reside very near their mobilization thresholds and may be mobilized by extremely low accelerations as well. For given acceleration, lower seismic frequencies are more efficient in liberating the ganglia. © 2006 Society of Exploration Geophysicists.
Keywords: FLOW THROUGH POROUS MEDIA; GEOPHYSICAL FLUID DYNAMICS; OIL DRILLING; ROCKS; SEISMIC WAVES